The 7 Trigger's to Yes : The New Science Behind Influencing People's - Russell H. Granger (Tata McGraw-Hill, 2008)
How can anyone persuade anybody to do anything? Let us count the ways Groundbreaking studies of the brain have revealed fascinating new data about the science of persuasion. This research proves that reason is not the best way to get people on your side. The 7 Triggers to Yes reveals how it's more effective to activate one of the seven key ;triggers that can cause an automatic ;yes decision. With this system, you'll be able to get commitment and results from others. Using the latest technological data, Granger gives the complex art of persuasion the ease of paint-by-numbers clarity and a process for success